A política econômica neoliberal como uma das causas de um impeachment: um estudo de caso sobre o impedimento da presidenta Dilma Rousseff - Seleghim, Ariane Duarte (Universidade Federal de São Carlos, 2021)
This thesis aims to contribute to research in Political Science that focuses on the explanatory factors of the 2016 impeachment. We use the process tracing method to gather empirical evidence to support the thesis that the resistance of Dilma Rousseff’s administration to deepen and radicalize neoliberal measures were part of a causal mechanism, a necessary condition that resulted in the president's deposition. We go back to the impeachment’s conjecture and its specificities. We observe the main factors that contributed to the impeachment giving more emphasis to the divergences of the government's economic policy in facing the economic crisis and recession. For this, we collected evidence that served to strengthen the argument within the research hypothesis. We develop a political content analysis based on the criteria and categories established by MARPOR in the government programs: "More Changes, More Future", by Former President Dilma Rousseff and “A Bridge to the Future” by her successor Michel Temer. At this stage, we were able to measure the relevance of the different categories of economic policy in each program. In addition, it enabled us to verify that there was a great divergence between the promises made by Dilma Rousseff and Michel Temer regarding the directions they would take toward economic policy. The empirical analysis was divided into two stages: i) a statistical analysis of the political content of the two programs, based on the same pre-established categorization proposed by MARPOR. This first part focuses on the justifications within the legislative proposals of each administration in order to build a measure to establish the differences in each program regarding neoliberal reforms; ii) a comparative analysis between what was promised in President Dilma Rousseff’s government program with respect to economic policy and what was actually done in the legislative agenda. We aim to verify that the divergences between what was promised and what was practiced by Rousseff’s administration is related to the loss of the president's base of support, another necessary condition for the impeachment. We conclude that, among the many factors that may explain the 2016 impediment, the resistance of Dilma Rousseff’s administration to deepening neoliberal policies and its austerity measures was a necessary condition for this result.
Neoliberal economic policy as one of the causes of an impeachment: a case study on president Dilma Rousseff's impediment
Keywords: Impeachment; Política econômica de governo; Neoliberalismo; Austeridade; Process tracing; Government economic policy; Neoliberalism; Austerity; CIENCIAS HUMANAS::CIENCIA POLITICA::ESTADO E GOVERNO